BlackBerry Bold Made Simple - Trautschold, Martin (Apress, 2012)
A book like this takes many people to put together. We would like to thank Apress for believing in us and our unique style of writing. We would like to thank our Editors, Jim and Laurin, and the entire editorial team at Apress. We would like to thank our families for their patience and support in allowing us to pursue projects such as this one.